Consensus clinical management guideline for beta‐propeller protein‐associated neurodegeneration. (4th August 2021) - Wilson, Jenny L; Gregory, Allison; Kurian, Manju A; Bushlin, Ittai; Mochel, Fanny; Emrick, Lisa; Adang, Laura; ,; Hogarth, Penelope; Hayflick, Susan J
Abstract : This review provides recommendations for the evaluation and management of individuals with beta‐propeller protein‐associated neurodegeneration (BPAN). BPAN is one of several neurodegenerative disorders with brain iron accumulation along with pantothenate kinase‐associated neurodegeneration, PLA2G6‐associated neurodegeneration, mitochondrial membrane protein‐associated neurodegeneration, fatty acid hydroxylase‐associated neurodegeneration, and COASY protein‐associated neurodegeneration. BPAN typically presents with global developmental delay and epilepsy in childhood, which is followed by the onset of dystonia and parkinsonism in mid‐adolescence or adulthood. BPAN is an X‐linked dominant disorder caused by pathogenic variants in WDR45, resulting in a broad clinical phenotype and imaging spectrum. This review, informed by an evaluation of the literature and expert opinion, discusses the clinical phenotype and progression of the disease, imaging findings, epilepsy features, and genetics, and proposes an approach to the initial evaluation and management of disease manifestations across the life span in individuals with BPAN. What this paper adds The complex epilepsy profile of beta‐propeller protein‐associated neurodegeneration (BPAN) often resolves in adolescence. The treatment for an individual with BPAN is supportive, with attention to sleep disorders, complex epilepsy, and behavioral problems. Individuals with BPAN have shifting needs throughout their life span requiring multidisciplinary care. What this paper adds: The complex epilepsy profile of beta‐propeller protein‐associated neurodegeneration (BPAN) often resolves in adolescence. The treatment for an individual with BPAN is supportive, with attention to sleep disorders, complex epilepsy, and behavioral problems. Individuals with BPAN have shifting needs throughout their life span requiring multidisciplinary care. podcast : (https://youtu.be/NUF4DJXVlWw )